Meriwether Lewis, boy explorer - Bebenroth, Charlotta M., 1890-; Fiorentino, Al (New York : Aladdin Paperbacks, 1997)
Relates events from the childhood and youth of the boy who grew up to become an explorer of the American West.
Originally published: Indianpolis : Bobbs-Merrll, [1962].
Keywords: Lewis, Meriwether, -- 1774-1809 -- Childhood and youth -- Juvenile literature; Lewis, Meriwether, -- 1774-1809 -- Childhood and youth; Explorers -- West (U.S.) -- Biography -- Juvenile literature; Explorers; West (U.S.) -- Discovery and exploration -- Juvenile literature